Exercise-based smoking cessation interventions among women - Linke, Sarah E (Womens Health (Lond), 2013)
Although smoking rates are lower among women than men, women are less likely to quit smoking in cessation trials. This is in part due to their tendency to smoke to help prevent or mitigate negative mood/affect, depression and/or postcessation weight gain. Exercise helps to alleviate women’s fear of postcessation weight gain and reduces their cessation-related mood symptoms, making it a theoretically ideal smoking cessation intervention for women. In addition, short bouts of exercise decrease cigarette cravings and withdrawal symptoms among temporarily abstinent smokers. However, results from exercise-based smoking cessation interventions to date have been mostly nonsignificant. This paper describes the theoretical mechanisms (psychological, behavioral, physiological and neurobiological) and practical reasons underlying our belief that exercise-based smoking cessation interventions should not yet be abandoned despite their current paucity of supporting evidence. It also presents ideas for modifying future exercise-based smoking cessation interventions to increase adherence and, as a result, more accurately evaluate the effect of exercise on smoking cessation.